Health literacy and associated factors in China: findings from the Wa ethnic group - Yang, Wanqiu; Liu, Yi; Zhang, Guangjie; Yao, Yu; Wang, Yanqing; Leng, Dan; Li, Chaoxiao; Liu, Kunjie; Liu, Jiazhou; Pu, Yongjie; Li, Mufei; Yang, Borui; et al. (Frontiers in Public Health, 2024)
Background The health literacy of ethnic groups in remote areas of China is far from satisfactory. However, the health literacy of ethnic groups in China remains unclear. This study aimed to explore the health literacy of the “advancing directly” ethnic group and its influencing factors. Methods A cross-sectional study was conducted using a staged sampling method among the Wa ethnic group, who have rapidly transitioned directly from the traditional lifestyle of slash-and-burn cultivation to modern societies. We used the Health Literacy Questionnaire (HLQ) to assess health literacy. We defined low health literacy as less than 60% of the total score and adequate health literacy as more than 80% of the total score. Results A total of 668 individuals met the inclusion criteria and the mean age was 42.19 (SD 10.56) years. The mean HLQ total score was 29.9 (SD 10.56). The prevalence of adequate health literacy was 0.89%. There were significant differences between the low and the non-low health literacy groups in terms of gender, age, education, marital status, occupation, residing place, current smoking status, and waist circumference (all p < 0.05). Multiple linear regression analysis showed that women (t = 9·418, p < 0.001), older age (B = −0.0091, t = −2.644, p = 0.008), low educational level (B = 0.766, t = 6.018, p < 0.001), current smoking (B = −2.66, t = −3.038, p = 0.008), and residence far from township (B = −5.761, t = −4.1, p < 0.001) were associated with low HLQ total score. Conclusion Our findings suggest that the health literacy of the Wa ethnic group is far from favorable. It indicates the need for increased efforts in improving the health literacy of “advancing directly” ethnic groups.